Pengaruh Memorable Tourism Experience terhadap Kepuasan Wisatawan dan Niat Berkunjung Kembali di Desa Wisata Penglipuran - Dewi, Mega Intan Puspita; Tirtawati, Ni Made; Liestiandre, Hanugerah Kristiono (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2023)
Memorable Tourism Experience is one of the sources that can be an aspect of excellence for destinations because memorable experiences will last for a long time. This will have an impact on tourist satisfaction and increase tourist loyalty to revisit intention . In the Penglipuran Tourism Village, this study was done to ascertain the impact of memorable tourism experiences on tourist satisfaction and revisit intention. This study fills a gap in the prior research by examining the impact of memorable tourism experiences on tourist satisfaction and revisit intention in Penglipuran Tourism Village. The sampling technique uses purposive sampling technique by distributing questionnaires to 170 domestic tourists who have visited Penglipuran Tourism Village at least twice. This type of research uses a quantitative approach with sampling techniques through questionnaires with Likert scales and data analysis using SEM-PLS. The study's findings indicate that there is no significant direct influence between variables related to the memorable tourism experience and revisit intention, but there is a significant direct influence between memorable tourism experience and tourist satisfaction, and there is a significant direct influence between tourist satisfaction and revisit intention, as well as a significant direct influence between tourist satisfaction and the memorable tourism experience.